2011
DOI: 10.1186/1475-9276-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in the use of physician services in Norway before and after introducing patient lists in primary care

Abstract: BackgroundInequity in use of physician services has been detected even within health care systems with universal coverage of the population through public insurance schemes. In this study we analyse and compare inequity in use of physician visits (GP and specialists) in Norway based on data from the Surveys of Living Conditions for the years 2000, 2002 and 2005. A patient list system was introduced for GPs in 2001 to improve GP accessibility, strengthen the stability of the patient-doctor relationship and ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
5
20
1
1
Order By: Relevance
“…Our findings regarding differences in sociodemographic and lifestyle characteristics are in line with previous Scandinavian studies [1-3, 6, 10]. For example, data from Norway [2,3,10] have showed that people with high level of education and high income are more likely to have a private supplementary health insurance, and that private health insurance is an important contributor to inequities in health care utilization in specialist care. A recently published review of the literature on what characterize individuals with voluntary private health insurance in universal health care systems [2,3,6] supports that the probability of being privately insured increases with income and education level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings regarding differences in sociodemographic and lifestyle characteristics are in line with previous Scandinavian studies [1-3, 6, 10]. For example, data from Norway [2,3,10] have showed that people with high level of education and high income are more likely to have a private supplementary health insurance, and that private health insurance is an important contributor to inequities in health care utilization in specialist care. A recently published review of the literature on what characterize individuals with voluntary private health insurance in universal health care systems [2,3,6] supports that the probability of being privately insured increases with income and education level.…”
Section: Discussionsupporting
confidence: 91%
“…During the last decade there has been a remarkable growth in private supplementary health insurance in Norway, especially employment-based private health insurance [1][2][3]. Most of the health care provided by private hospitals has public funding through contracts with the public regional health authorities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 Of course, if individuals move to another municipality they are also allowed to switch GP across municipalities. 9 4 Data…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Therefore, all available (survey) information on patient need is included as controls. In comparative studies, di¤erences are detected between countries with di¤erent health care systems, but in most developed countries, specialist visits is distributed in favour of high-income individuals while GP visits are more equitably distributed (Grasdal and Monstad, 2011). 5 The key contributions of our paper to the existing literature are the following.…”
Section: Introductionmentioning
confidence: 99%